Q: What is x in 12x plus 6 equals 6x plus 48?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

6x+7 = -56x = -12x = -2

8x-3+6x-1 = 12x+614x-4 = 12x+614x-12x = 6+42x = 10x = 5

12x-41=6x+1 add 41 to both sides 12x=6x+42 subtract 6x from both sides 6x=42 divide both sides by 8 x=7

2x + 6x + 4x = 12x

55 = 6x + 7 so 48 = 6x so 8 = x

Related questions

10+12x=-14 -14-10=12x 12x=-24 x=-2

6x + 12x + 2x = 80 20x = 80 x = 4

6x+7 = -56x = -12x = -2

8x-3+6x-1 = 12x+614x-4 = 12x+614x-12x = 6+42x = 10x = 5

-6x + 20.4 = 48 -6x = 48 - 20.4 -6x = 27.6 x = -4.6

12x-41=6x+1 add 41 to both sides 12x=6x+42 subtract 6x from both sides 6x=42 divide both sides by 8 x=7

6x+4=52 6x=48 x=8

2x + 6x + 4x = 12x

55 = 6x + 7 so 48 = 6x so 8 = x

2

If: 6x = 48 Then: x = 8

(6x^5 + 12x) / (-2x^-3) =[ (6x^5 + 12x) (x^3) ] / (-2) =(6x^8 + 12x^4) / (-2)=(3x^8 + 6x^4) =(3x^4)[ (x^4) + 2 ]